Scalable interrogation: Eliciting human pheromone responses to deception in a security interview setting. (March 2015) - Stedmon, Alex W.; Eachus, Peter; Baillie, Les; Tallis, Huw; Donkor, Richard; Edlin-White, Robert; Bracewell, Robert
Abstract: Individuals trying to conceal knowledge from interrogators are likely to experience raised levels of stress that can manifest itself across biological, physiological, psychological and behavioural factors, providing an opportunity for detection. Using established research paradigms an innovative scalable interrogation was designed in which participants were given a 'token' that represented information they had to conceal from interviewers. A control group did not receive a token and therefore did not have to deceive the investigators. The aim of this investigation was to examine differences between deceivers and truth-tellers across the four factors by collecting data for cortisol levels, sweat samples, heart-rate, respiration, skin temperature, subjective stress ratings and video and audio recordings. The results provided an integrated understanding of responses to interrogation by those actively concealing information and those acting innocently. Of particular importance, the results also suggest, for the first time in an interrogation setting, that stressed individuals may secrete a volatile steroid based marker that could be used for stand-off detection. The findings are discussed in relation to developing a scalable interrogation protocol for future research in this area. Highlights: For the first time a stress pheromone was identified in deception interrogations. Participants concealing information responded differently to innocent participants. Biological, physiological, psychological and behavioural stress data were collected. This research validated a unique scalable interrogation paradigm.